EVOLUTION OF ASSET ATTRIBUTION IN FINOPS: ANALYZING ENTERPRISE APPROACHES IN THE MULTI-CLOUD ERA - Raghu Venkatesh, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article examines the divergent approaches to cloud asset attribution between cloud-native and traditional enterprises, analyzing implementation patterns across 147 organizations over 24 months (2022-2024). Through mixed-method analysis combining quantitative cost data and qualitative organizational assessments, this article reveals that cloud-native enterprises achieve 94% asset attribution accuracy within six months of implementation, compared to 67% in traditional enterprises. The article demonstrates that automated tagging frameworks, combined with real-time cost allocation systems, reduce unattributed cloud spend by an average of 42% (p < 0.001). However, traditional enterprises face significant challenges, with 73% reporting difficulties integrating attribution systems with legacy infrastructure. The findings indicate that successful asset attribution implementations correlate strongly (r = 0.78) with organizational FinOps maturity levels, particularly in automation and cross-functional collaboration. The article contributes to the growing body of FinOps literature by establishing empirical benchmarks for attribution success factors and proposing a novel framework for enterprise cloud cost management.